Maffesoli e a "investigação do sentido" - das identidades às identificações - Eduardo Portanova Barros (Ciências Sociais Unisinos)
Michel Maffesoli¿s work tries to understand the common man without despising him as something insignificant if compared to the researcher of academic formation. For that inclination we can discuss a theme that, for him, has deserved several reflections: the passage from an identity way (ideological connotation) to an identification form (imaginal connotation, that concerns the imaginary). The identity would be a characteristic of the modernity, while the identification would be a characteristic of the post-modernity. Let us see why. Maffesoli works with the theory of a post-modern sensibility to see changes in the civilization. It is a prospective type of reasoning, like Nietzsche's. Of all the post-modern affiliation theorists, Maffesoli is the only one that tries to include the imaginary, under the durandiano view, in his form of thinking. And it is that, precisely, the peculiarity of his work, a reflection on the new "social dynamics" . For him, the difference is clear. If we were able to have a delineated profile, a safe profession, a life project before, that no longer happens. Now, profiles are mutant, professions (almost) do not exist, projects are occasional and the future, uncertain. What is worth is the present (presenteism). The subject of the identity deserves a long reflection on the part of Maffesoli. This theme is also discussed by other theorists linked to the Cultural Studies, like Stuart Hall. Maffesoli argues, approaching Hall, and vice-versa, that a saturation of the classical logics of identity can happen.